Pharmacokinetics of ceftibuten-cis and its trans metabolite in healthy volunteers and in patients with chronic renal insufficiency. - Kelloway, J S (1991)
The impact of renal insufficiency on the dispositions of 300 mg of orally administered ceftibuten-cis, a new broad-spectrum oral cephalosporin, and its primary metabolite ceftibuten-trans was characterized in 30 adult subjects. Subjects were divided into five groups of six subjects each on the basis of their 24-h ambulatory creatinine clearances (CLCR). The apparent total body clearance (CLP/F; where F is absolute bioavailability) and renal clearance of ceftibuten-cis were significantly lower in subjects with end-stage renal disease (on maintenance hemodialysis; group V) and in those with severe (CLCR, 5 to 29 ml/min; group IV) and moderate (CLCR, 30 to 49 ml/min; group III) renal insufficiency than in those with mild renal insufficiency (CLCR, 50 to 80 ml/min; group II) or normal renal function (CLCR, greater than 80 ml/min; group I). A significant correlation was observed between CLCR and ceftibuten-cis CLP/F. The mean apparent steady-state volume of distribution (V beta/F) of ceftibuten-cis ranged from 0.21 to 0.24 liter/kg in subjects in group I, II, III, and IV. V beta/F was significantly greater in the group V subjects with end-stage renal disease (V beta/F, 0.39 +/- 0.27 liters/kg). These changes in V beta/F cannot be separated from possible changes in bioavailability. The maximum concentration of ceftibuten-trans in plasma was significantly higher and occurred significantly later in group IV subjects than it did in subjects in the other groups.(ABSTRACT TRUNCATED AT 250 WORDS)